Partial Sums of Two Quartic q-Series - Chu, W.; Wang, C. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
The partial sums of two quartic basic hypergeometric series are investigated by means of the modified Abel lemma on summation by parts. Several summation and transformation formulae are consequently established.